Impact Of Psychological Contracton Employer Employee Relationship In Corporate Sector - Pratap, Nibha (Gyan Management Journal, 2020)
The objective of paper is to  review the  concept of psychological  contract and study its impact on  employee-employer relationship. Typical employer-employee relationships will vary on the scale of  closeness and familiarity but it is typically guided by formal agreements, be they individual letters of  understanding, management contracts or the government legislation that sets the standards for fair  and  im-partial  work.  But there  is  another  contract that  can  be  even  more  important  called the  psychological contract. A psychological contract, a concept developed in contemporary research by  organizational scholar  Denise  Rousseau,represents  the  mutual  beliefs,  perceptions,  and  informal  obligations between an employer and an employee. It sets the dynamics for the relationship and defines  the  detailed  practicality  of  the  work  to  be  done.The  psychological  contract  may  be  very  well  understood as an informal understanding of the relationship between an employer and employee. It is  a belief that that there is a promise between both parties and hence agree to abide by, such as mutual  expectations of honesty, respect, fairness, loyalty and dedication. It is an unwritten and unlike the  written contract, it is constantly at change. By nature it is generally unspoken and hence dependent on  the interpretation of all parties. The paper will help us to understand the concept of psychological  contract  and  employee-employer  relationship  and impact  of  psychological  contract  on  employee employer relationship.
Keywords: Psychological Contract; Employee-Employer Relationship